2011
DOI: 10.3174/ajnr.a2823
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measurements: Effect of CT Depth of Pretracheal Soft Tissue on Tracheotomy Tube Selection

Abstract: BACKGROUND AND PURPOSE:Tracheotomy is a commonly performed procedure; however, in the obese, it can be associated with a high morbidity and mortality, partially due to accidental decannulation. We hypothesize that a simple and rapid measurement of the DPST on CT will accurately predict those patients in need of an extended-length tracheotomy tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Patients from the IABP group had a greater duration of inotrope use (51 hours vs 39 hours [25-66], P = 0.007) and longer intensive care unit length of stay (five days [3][4][5][6][7][8] vs four days [3][4][5][6], P = 0.035). The length of hospital stay was similar (13 days [9][10][11][12][13][14][15][16][17][18] vs 11 days [8][9][10][11][12][13][14][15][16][17], P = 0.302) between groups. Conclusions: Preoperative IABP use did not reduce 30-day major complications in high-risk patients undergoing cardiac surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients from the IABP group had a greater duration of inotrope use (51 hours vs 39 hours [25-66], P = 0.007) and longer intensive care unit length of stay (five days [3][4][5][6][7][8] vs four days [3][4][5][6], P = 0.035). The length of hospital stay was similar (13 days [9][10][11][12][13][14][15][16][17][18] vs 11 days [8][9][10][11][12][13][14][15][16][17], P = 0.302) between groups. Conclusions: Preoperative IABP use did not reduce 30-day major complications in high-risk patients undergoing cardiac surgery.…”
Section: Methodsmentioning
confidence: 99%
“…68.2% of patients in the intervention group were compliant ] with a median adherence to the NAVA mode of 87.5% [38. 9,99]. Ventilator free days to day 28 were 18 [8,24] days in the NAVA group vs. 19 [0, 23] days in the PSV group.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric studies using chest radiograph, neck USG, and CT anticipates unconventional extended-length tracheostomy tubes with adjustable flanges when skin-trachea distance was > 4.4 cm. [7][8][9] Ahuja et al reported the use of endotracheal tube in a difficult tracheostomy scenario arising secondary to surgical emphysema. 10 It can be tried in such dire emergencies when specialized tracheostomy tubes are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…長期間の人工呼吸器管理を要する症例や気道狭窄,閉塞を伴う症例では気管切開を行うことが多い。気管切開後の気道におけるトラブルは致死的となる可能性が高く,日本医療安全調査機構も,気管切開後の気管カニューレの逸脱,迷入について提言を発している 1)。また,高度の肥満や気管の偏位を伴う症例では,皮下組織への逸脱,迷入など,周術期合併症が有意に上昇するとの報告もある 2), 3), 4), 5)。これらの問題に対応するべく,横山らは新型気管カニューレとして,アジャストフィット(AF) ® (富士システムズ株式会社)を開発している 6)。AFはウイングとチューブが独立しており,アジャスタにて両者を固定する(Fig. 1)。そのため,ウイングの位置を調整することで,気管内に挿入するチューブの長さを自由に変更することができ,皮下脂肪が極端に厚い,もしくは薄い症例でも柔軟な対応が可能となる。また,シリコン製のスパイラルチューブであるため,気管の形に合わせて変形し,気管壁への刺激を軽減することができる。しかし,複数の症例を集積し,AFの有用性や有害事象を考察したうえで,適応についてまで検討した報告は少ない。…”
Section: 背  景unclassified